Evaluación de dos cepas comerciales de entomonematodos como agentes de control de Cyrtomenus bergi Froeschner (Hemiptera: Cydnidae) - Melo Molina, E.L.; Ortega Ojeda, CA; Gaigl, A; Ehlers, R.U.; Bellotti, Anthony C. (2006)
Cyrtomenus bergi Froeschner is a subterranean phytophage important in tropical crops. We tested two commercial entomopathogenic nematode (epn) strains (Steinernema feltiae (Filipjev) and Heterorhabditis bacteriophora Poinar) as biological antagonists in the greenhouse (18-28°C and 55-85% relative humidity). We used the concentrations recommended by the supplier E-nema: 1000 and 500 epn/ ml of S. feltiae and H. bacteriophora, respectively. These solutions were applied to pots of 1,5 dm3 filled with agricultural soil and sand (1:1) with 20 burrower bugs (adults or 5th instar immatures) confined to each pot. The insects were fed on groundnuts (Arachis hypogaea L.). Infestation rate of the burrower bug and mortality were measured through destructive evaluations 15 and 30 days after application (daa), three pots per time period. Only adults were infested (P£0,05). Considering both evaluations and all strains, we observed the greatest penetration rate for S. feltiae (93,9%) compared to H. bacteriophora (72,1%). In terms of mortality, H. bacteriophora killed more bugs after 15 days (42,2%) than S. feltiae (8,6%); however, after 30 days no differences were found between the two epn strains (54,3%). Moreover, we observed melanized nematodes, probably as an immune response of C. bergi against nematodes, where S. feltiae (37,5%) was more susceptible than H. bacteriophora (13,1%) at 30 daa. We conclude that only adults of C. bergi are susceptible to entomonematodes; H. bacteriophora is the most promising strain for producing greater mortality in less time and presenting a lower percent of melanization under these conditions.